Towards a Palestinian State : Reforms for Fiscal Strengthening - World Bank (Washington, DC, 2017)
The thirteenth government of the Palestinian Authority (PA) presented in August 2009 a program entitled Palestine: ending the occupation, establishing the state (hereafter referred to as the program) that lays out the vision, foundational principles, and national goals for the future Palestinian state, as well as institution-building and sector priorities. This report will therefore begin by discussing recent trends in the economic restrictions imposed by the Government of Israel (GoI) on West Bank and Gaza (WB&G). The next section will focus on an analysis of economic and fiscal developments, highlighting the fact that WB&G experienced in 2009 a third consecutive year of economic growth and rising per capita GDP, driven by large inflows of external assistance and a relatively stable security situation. Despite the growth, however, the recurrent deficit rose from roughly US$1.3 billion in 2008 to US$1.6 billion on a commitment basis in 2009, mostly as a result of emergency spending in Gaza in the aftermath of Israel s military operation (operation cast lead, December 27, 2008, January 18, 2009) as well as arrears brought forward from 2008 and recognized as commitments in 2009. Given this finding, the discussion in remainder of the report is particularly relevant, focusing on the reform areas of fiscal strengthening and improved public financial management and the important role played by local governments in this regard.